4CPS-384 Potential drug related problems in the time of COVID-19. (14th March 2021) - Barceló-Vidal, J; Carballo, N; De Antonio-Cuscó, M; Fernández-Sala, X; Echeverría-Esnal, D; Acín, P; López-Mula, C; Comella-Anaya, L; González-Colominas, E; Luque, S; Ferrández, O
Abstract : Background and importance: Drug related problems (DRP) are common among hospitalised patients. During the COVID-19 pandemic, the number of inpatients increased and the pattern of drug use was varied which could lead to a higher number of potential DRP. Aim and objectives: To describe DRP in patients admitted to COVID-19 wards during the COVID-19 pandemic peak. Material and methods: A retrospective observational study was performed in a tertiary university hospital from 21 March to 30 April 2020. Patients included were those admitted to a COVID-19 ward and presenting a DRP (excluding emergency department and critical care units). Computerised physician order entry (CPOE) operates for all hospital beds. Medical prescriptions were revised daily by clinical pharmacists. When a potential DRP was detected, an annotation with a recommendation was made in the patient's medical record. DRP were classified according to the Pharmaceutical Care Network Europe classification. Data collected were demographic, the drug class involved (anatomical chemical therapeutic (ATC)), DRP detected and degree of recommendation acceptance. Results: Total patients with DRP: 291 (23.3%). Identified DRP: 393 (1.4 DRP/patient). 58.3% were men and median age was 63 (15.7) years. Conclusion and relevance: Almost 25% of all patients had a DRP, presenting an incidence of 1.4 DRP/patient, higher than reported in previous series. 83% of evaluable recommendations were accepted. One- third of the recommendations were derived from a wrong dosage, and 15% from drug interactions. Hydroxychloroquine was the most frequently involved drug, probably because of the limited experience and wide spectrum of interactions, followed by antimicrobials such as ceftriaxone and azithromycin, used widely in respiratory tract infections. References and/or acknowledgements: Conflict of interest: No conflict of interest